2016
DOI: 10.1590/1807-3107bor-2016.vol30.0087
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on clinical and microbial analysis of periodontal status in pregnancy

Abstract: This study was aimed to provide a longitudinal overview of the subgingival bacterial microbiome using fluorescence in situ hybridization (FISH) technique, in women in the second trimester of pregnancy (between 14 and 24 weeks), and 48 h and 8 weeks postpartum. Of 31 women evaluated during pregnancy, 24 returned for the 48-h and 18 for their 8-week exams postpartum. Probing depth (PD), bleeding on probing, clinical attachment level, and presence of calculus were recorded. Subgingival plaque samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…The prevalence of dental caries reaches 89% in adults aged 30 to 40 years in the country [25]. In addition, pregnant women demonstrate inflammation of periodontal tissues [26]. Moreover, there is high distribution of dental problems (69-72%) among pregnant women [12].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dental caries reaches 89% in adults aged 30 to 40 years in the country [25]. In addition, pregnant women demonstrate inflammation of periodontal tissues [26]. Moreover, there is high distribution of dental problems (69-72%) among pregnant women [12].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of Prevotella spp. and pre`gnancy has been widely reported [14,29]. Dareen Fteita and his colleague have reported that Prevotella nigrescens, Prevotella pallens and Prevotella aurantiaca, which are similar to Prevotella intermedia, have a higher relative abundance as estradiol levels increase during pregnancy [30].…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting findings as to whether hormone‐mediated changes in oral microbial balance contribute to periodontal exacerbations during pregnancy. Some have observed changes in the microbiome corresponding to hormonal changes during pregnancy, while others have reported no differences . Differences in study design, the bacterial species investigated, sampling methods and approaches to bacterial identification could account for such heterogeneity.…”
Section: Biological Mechanismsmentioning
confidence: 99%